Answer:
10.7x + 5
Step-by-step explanation:
(3.5x - 5) + (7.2x + 10)
Take out the parenthesis so it can be easier to see
3.5x - 5 + 7.2x + 10
Combine like terms
(3.5x and 7.2x) and ( -5 and 10)
10.7x + 5
And you cannot simplify it anymore
Hope this helped!
Have a supercalifragilisticexpialidocious day!
Answer:6,2
Step-by-step explanation:you need to add each step and divide
Is there any sums that you needed to solve this with?
<h3>
Answer: 1</h3>
Explanation:
The jump from 2 to 2&1/2 is an increase of 1/2
2 + 1/2 = 2 & 1/2
The jump from 2 & 1/2 to 1 & 1/2 is a decrease of 1
(2 & 1/2) - 1 = (2 - 1) & 1/2 = 1 & 1/2
The jump from 1 & 1/2 to 2 is an increase of 1/2
(1 & 1/2) + 1/2 = 1 + (1/2 + 1/2) = 1 + 1 = 2
The pattern seems to be "add 1/2, subtract 1". Assuming this is the case, we would then subtract 1 from the last term we got (2) to get 2-1 = 1